OUTCOMES OF BALLOON KYPHOPLASTY FOR THE TREATMENT OF OSTEOPOROTIC VERTEBRAL COMPRESSION FRACTURES AT SON LA PROVINCIAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe patient characteristics and evaluate pain; function, and radiographic changes after balloon kyphoplasty for osteoporotic vertebral compression fractures (OVCF).Materials and methods: A pre–post case series of 56 OVCF patients treated at Son La Provincial General Hospital (01/2024–03/2026). Pain and disability were assessed using the Visual Analog Scale (VAS) and Roland–Morris Disability Questionnaire preoperatively, postoperative day 1, month 1, and month 3. Radiographic outcomes included wedge angle, Cobb angle, and vertebral body heights (anterior/middle/posterior). Paired t-tests compared pre–post values (p
Keywords: osteoporotic vertebral compression fracture; balloon kyphoplasty; cement leakage; VAS; Roland–Morris.